The gap in medical education: the missing element of digital health economics education - a prospective cross-sectional pilot study - Hertling, Stefan; Loos, Franziska; Bambina, Fabrizio; Schöffski, Oliver; Graul, Isabel; Schleussner, Ekkehard (Frontiers in Medicine, 2025)
BackgroundThe increasing economization of healthcare requires greater integration of health economics content into medical education.ObjectiveThis study examines medical students’ attitudes toward health economics and their preferred teaching formats.Materials and methodsThis prospective cross-sectional pilot study is based on a survey of medical students at the 36 medical faculties in Germany between April and October 2021. For this purpose, questionnaires were established. We received feedback from the participating students through two 24-point questionnaires.Results3042 students of human medicine took part. The results reveal a significant gap in education and care: 75% of respondents consider their knowledge to be insufficient, while 93% are in favor of digital teaching formats such as e-learning. Significant differences in approval are evident according to age and stage of study, but not according to gender. Based on these results, the concept of digital health economics education (DHEE) is proposed as a forward-looking teaching concept that conveys health economics content digitally, interdisciplinarity and in a way that is firmly anchored in the curriculum. This form of learning offers great potential for addressing structural challenges such as resource scarcity, increasing economic pressure to make decisions and a lack of management skills in everyday medical practice. Close cooperation between medicine and health economics in research and teaching is required to enable sustainable integration into the curriculum.